Studies in molecular weight determination of rubber seed oil alkyds - Okieimen F E; Aigbodion A I (Industrial Crops and Products, 1997)
Molecular weights of six samples of rubber seed oil alkyds having oil content of 20;(I), 30;(II), 35;(III), 40;(IV), 50;(V), and 60;(VI) prepared with phthalic anhydride, glycerol and rubber seed oil were specific gravity 0.926, colour 0.5R 10Y, free fatty acid 11.29, peroxide value 0.40, saponification value 192.93, iodine value 155.56 and unsaponifiable matter (;) 0.84. Average molecular weights determined, ranged from 441.11 for sample III to 1323.33 for sample V and those calculated range from 1165.52 for sample I to 4769.52 for sample IV. Although average molecular weights calculated were found to be larger than the values determined, Rast method seems to be a more reasonable method of average molecular weight determination for routine analysis. The differences obserrved were attributed to the assumption that only interesterification reactions occur during alkyd preparation in calculating average molecular weights. Fractionation of the alkyds showed that rubber seed oil alkyds consists of fractions of varying molecular weights. Study of molecular weight distribution showed that species of low average molecular weight constitute greater proportion of the alkyds. Average molecular weights of the final alkyds vary with the amounts of reactants used in the preparation. Ability of a thin layer of the alkyds to air-dry was found to be dependent on solid content, viscosity of alkyd solution and level of unsaturation in the final alkyd. Thus alkyds containing 40;rubber seed oil and above were found to be air-drying while those containing lower oil content are considered suitable in formulating baked finishes or can be combined with other film-forming resins.
Keywords: Alkyd resin; Endgroup analysis; Rubber seed oil; Saponification value